Using ethnography to access, understand, and reflect on video observation of violence - Friis, Camilla Bank (Fieldwork experiences in criminology and security studies, 2023)
Video observation holds great potential for changing our understanding of crime and violence. Recordings of real-life violence provide a detailed and uninterrupted perspective on patterns of actual behavior. This enables the possibility to analyze systematically and reliably what happens in violent interactions caught on camera. Video observational studies are mainly focused on the findings of what is observed in the videos. Yet, scholars who draw on footage from CCTV and body-worn cameras use ethnographic tools and emotions to gain access, analyze, and contextualize the content of these recordings. These tools and emotions are rarely reflected upon in research papers based on video observation despite their necessity for accessing videos, interpreting them in meaningful ways, evaluating, and ethically communicating the results. In this chapter, we look behind the scenes of doing video observation on violence. Drawing on four projects based on footage from CCTV and body-worn cameras, we show how we accessed, understood, and reflected on video observation of violent interactions using ethnographic tools. Further, we illustrate some of the ethical dilemmas involved in this process. We end the chapter with three lessons for future scholars who want to conduct video observation of real-life conflict interactions with CCTV and body-worn cameras.